Anti-Crime Programs: An Evaluation of the Comuna Segura Program - Benavente, José Miguel; Contreras, Dante; Montero, Rodrigo (Estudios de Economía, 2016)
The aim of this paper is to evaluate the impact that the anti-crime program Comuna Segura: Compromiso 100 had on the reporting rate of different types of crimes. This program, implemented in Chile starting in 2001, was very highly criticized and, therefore, was eliminated in 2006. This paper provides statistical evidence, using the impact assessment methodology, which shows that the program was successful in increasing the reporting rate in targeted municipalities and also in decreasing levels of crimes associated with other crimes, such as rape. All this underlies the importance of carrying out formal impact assessments in order to determine benefits that are associated with a particular program. However, financial issues are also very important too and it is necessary to take them in account when making a fair statement about the cost-effectiveness of the program. This point is, however, not addressed in this paper but should be kept in mind in order to have a complete picture of the program.